The Impact of The Covid 19 Pandemic on Audit Quality - Jean Stevany Matitaputty; Noegroho Yefta Andi Kus (Postgraduate Program Merdeka University, 2024)
This study aims to investigate the impact of audit fees, going concern, audit procedures, human capital, and auditor salaries on audit quality during the Covid-19 pandemic. The population used in the study consists of all public accountants who are members of IAPI. A purposive sampling technique is employed to select the sample, which is surveyed using online questionnaires. Multiple linear regression is used to analyze the research data. The findings of the study indicate that audit fees, going concern, audit procedures, and human capital have a positive impact on audit quality, while auditor salary does not significantly affect audit quality JEL Classification: M42, M41, G02 DOI: https://doi.org/10.26905/afr.v7i3.12827